An empirical evidence of ethical climate index in rural banks from Board of Directors Perspective - Sunardi Sunardi; Hafid Aditya Pradesa (Journal of Economics, Business, and Accountancy Ventura, 2018)
The existence of the common image that the management of the rural bank isÂ  not yet professional because of some unethical practices are still happening. Rural bank that is well known for Indonesian people since its target markets are mostly in the rural area. The aim of the study is to investigate what are the most important factors that are reflecting ethical climate in rural banks. The studyinvolves 153Â  directors of rural banks in Indonesia as respondents. Confirmatory factor analysis (CFA) was used to assess individual parameters in the model, feasibility and the statistical significance of the estimates parameter. The findings show that that ethical climate index is most reflected by collective moral sensitivity, but in contrary boards of directors in rural banks also recognize the lowest perception in this dimension. This would sense an urgency to fostering moral sensitivity among all hierarchies, from top management to the lowest levels in the rural banking.